Impacts of combined or single supplementation of branched-chain amino acids on delayed onset muscle soreness and muscle damage following resistance exercise - Asjodi, Foad; Daryabeygi Khotbesara, Reza; Pourghassem Gargari, Bahram; Izadi, Azimeh (Progress in Nutrition, 2018)
The purpose of this investigation was to determine and compare the effects of leucine (Leu), valine (Val), isoleucine (Ilue), and combined branched chain amino acids (BCAA) supplementation, on markers of muscle damage following resistance exercise. It was hypothesized that supplementation would attenuate the levels of indirect muscle damage markers and muscle soreness following exercise-induced muscle damage, and facilitate the restoration of muscle function. A total of 50 untrained males were randomly divided into five groups; Leu (n = 10), Ilue (n = 10), Val (n = 10), BCAA (n = 10), and placebo (n = 10). The muscle damage protocol specific to non-athletes is used in the current study. A 500 ml of group-specific solution was given to each group in two time points, 30 minutes before and immediately after performing the exercise. Multivariate analysis showed significant time differences for LDH in all groups (p<0.05); there were significant multivariate time differences in all groups regarding creatine kinase (CK) (p=0.000 for all groups). A significant time differences observed in all groups regarding repetition maximum [RM] (p<0.01) and pain (p=0.000 for all groups). The results of this investigation show that compared to combined BCAA, Ilue or Val; Leu provides more protective effect on attenuating the immediate increase in biochemical markers of muscle damage following eccentric-based resistance exercise, while combined BCAA may aid to maintain the range of motion. Additionally the results showed that perceived pain by individuals in the placebo group was significantly higher compared to all other groups. Hence, BCAA intake, especially Leu, in the dosage used in this investigation is ergogenic for untrained males.